2019
DOI: 10.3390/ijerph16040647
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Swimming Training in Cold Water on Antioxidant Enzyme Activity and Lipid Peroxidation in Erythrocytes of Male and Female Aged Rats

Abstract: The aim of this study was to verify whether eight-week-long swimming exercise training would evaluate the level of selected indicators of the pro-oxidant/antioxidant status in response to cold water in comparison with swimming under thermoneutral conditions in sedentary male and female elderly rats. The exercise-trained groups swam four min/day and five days a week during eight weeks of housing. Exercise was performed by swimming in glass tanks containing tap water maintained according to group at 5 °C and 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…During the first week of the study, the duration of the first swim was 2 min and increased by 0.5 min per day up to 4 min on the fifth day of the first week. The duration of the single sessions was based on the results of other researchers who showed that rats would swim actively for up to 4 min in 4–5 °C water, and then only drift [ 25 ]. Based on literature data, it is known that rats at a thermally comfortable temperature can be active for much longer [ 26 ], and hence the choice of a 4-min daily swimming session for both study groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first week of the study, the duration of the first swim was 2 min and increased by 0.5 min per day up to 4 min on the fifth day of the first week. The duration of the single sessions was based on the results of other researchers who showed that rats would swim actively for up to 4 min in 4–5 °C water, and then only drift [ 25 ]. Based on literature data, it is known that rats at a thermally comfortable temperature can be active for much longer [ 26 ], and hence the choice of a 4-min daily swimming session for both study groups.…”
Section: Methodsmentioning
confidence: 99%
“…Increased synthesis of ROS may result in oxidative stress and cellular damage, such as in lipid peroxidation. In a previously cited study by Lubkowska et al (2019) [28] conducted on the same rat model, a significant increase of lipid peroxidation markers (such as thiobarbituric acid reactive substances (TBARS) and 8-isoprostane) in erythrocytes was demonstrated in the rats swimming in either cold water or thermally comfortable water, as well as in the control group. The increase in ROS synthesis may result in increased prostanoids synthesis through activation of cyclooxygenases (COX).…”
Section: The Role Of Low Temperature and Hormonal Regulation In Bone Mineral Metabolismmentioning
confidence: 99%
“…After 4 days, the blood glucose of rats was measured by tail punching method and based on fasting blood glucose and to homogenize, the diabetic rats were assigned in 1-control (C), 2-cinnamon (Ci), 3-swimming (S) and 4-swimming plus cinnamon (S + Ci) groups. Then, rats in the training groups were trained for six weeks, five sessions per week, five days a week, for two minutes in the first week, and in each training session, 30 seconds were added to the training until it reached 4 minutes (16). Also, rats in the cinnamon groups received the aqueous cinnamon extract orally at a dose of 200 mg per kg of animal body weight (17).…”
Section: Subjectsmentioning
confidence: 99%
“…This non-enzymatic antioxidant system protects blood components from oxidative damage and/or injury (4)(5)(6)(7). Several studies have suggested that this increased antioxidant capacity (8)(9)(10)(11) is needed to prevent oxidative stress (12).…”
Section: Introductionmentioning
confidence: 99%